Fiqh Teachers' Understanding in Gayo Lues on the Dual Role of Female Civil Servants - Ilhamani Ilhamani; Ali Abubakar; Ajidar Matsyah (Islamic Studies and Civilization Journal, 2025)
In the perspective of fiqh, both classical and modern, domestic work such as cooking, washing, cleaning the house, and so on is not the absolute obligation of the wife. Therefore, such work should not be entirely imposed upon her. However, female fiqh teachers of civil servants (ASN) in Gayo Lues, despite having professional responsibilities outside the home—where both husband and wife spend relatively equal time working in the public sphere—still bear the entire burden of domestic work, resulting in a double workload for the wife. This phenomenon of dual roles among female fiqh teachers of civil servants attracted the researcher's attention to conduct this study, analysing how their understanding of fiqh influences women's roles in the household. This study employs a qualitative method, with data analysis carried out through a descriptive-analytical approach using phenomenology. Data were collected through in-depth interviews as primary sources and literature study as secondary sources. The findings reveal that the dual roles of female ASN in Gayo Lues consist of public and domestic roles: as civil servants and breadwinners, while simultaneously acting as domestic workers. Almost all of them understand that domestic work is not the absolute obligation of wives, and that household responsibilities should be shared fairly in accordance with Islamic principles. However, this understanding has not yet succeeded in changing the unequal division of labour within households. Their understanding of fiqh has little influence on shaping their household roles, being overshadowed by cultural systems, gender norms, psychological pressures, economic conditions, and a less inclusive religious understanding. Therefore, the researcher recommends positioning fiqh not merely as a set of normative laws, but as a means of social transformation capable of adapting to the realities of contemporary women's lives.